Legal Consequences And Responsibility of Wa’ad Bonding Power to Sharia Compliance in Akad Al-Ijarah al-Muntahiyah Bi al-Tamlik - Mustofa Abdul Basir; Dian Prihanto; Idhofi Fahrizal; Neni Sri Imaniyati (Sharia and Law Faculty, 2022)
The existence of sharia bukan-bank financial institutions (NBFI) today is very important and one form of financing is al-Ijarah al-Muntahiyah Bi al-Tamlik (IMBT), which is a lease agreement (ijarah) with the transfer of ownership of the object that is used as a lease in when the IMBT contract ends which is based on the existence of wa’ad (promise). This research is a normative juridical research on the IMBT contract in the Fatwa of the National Sharia Council through analysis based on Islamic and Civil law. The nature of wa’ad in IMBT is that the law is not binding, this is contradictory to several arguments in the Qur'an and al-Hadith that command to fulfill and keep promises, which means the promise is binding. If wa’ad is carried out, the legal consequence is that rights and obligations arise between the lessee and the lessor to hand over and receive the object of the lease and violate the prohibition against making transactions in one contract. However, if the wa’ad is not implemented, the IMBT contract does not exist, there is only the Ijarah contract and the legal consequence is that the IMBT contract is null and void or considered to have never existed.Keberadaan lembaga keuangan bukan bank (LKBB) syariah dewasa ini sangat penting dan salah satu bentuk pembiayaannya adalah al-Ijarah al-Muntahiyah Bi al-Tamlik (IMBT) yang merupakan akad sewa menyewa (ijarah) dengan peralihan kepemilikan atas objek yang dijadikan sewa menyewa pada saat akad IMBT berakhir yang didasari atas adanya wa’ad (janji). Penelitian ini merupakan penelitian yuridis normatif atas akad IMBT dalam Fatwa Dewan Syariah Nasional melalui analisis berdasarkan hukum Islam dan Perdata. Sifat wa’ad dalam IMBT adalah hukumnya tidak mengikat, hal ini kontradiktif dengan beberapa dalil dalam al-Qur’an dan al-Hadits yang menyuruh untuk memenuhi dan menepati janji yang artinya janji itu mengikat. Jika wa’ad dilaksanakan maka akibat hukumnya adalah timbul hak dan kewajiban antara penyewa dan yang menyewakan untuk menyerahkan dan menerima objek sewa menyewa dan melanggar larangan melakukan transaksi dalam satu akad. Tetapi, jika wa’ad tidak dilaksanakan maka akad IMBT menjadi tidak ada, yang ada adalah akad Ijarah saja serta akibat hukumnya adalah akad IMBT batal demi hukum atau dianggap tidak pernah ada.